New perspectives for recycling dental zirconia waste resulting from CAD/CAM manufacturing process. (20th May 2017) - Gouveia, P. Faust; Schabbach, L.M.; Souza, J.C.M.; Henriques, B.; Labrincha, J.A.; Silva, F.S.; Fredel, M.C.; Mesquita-Guimarães, J.
Abstract: On modern prosthodontics, CAD/CAM technology is the main manufacturing technique to produce the all-ceramic restorations. Zirconia stabilized with 3%mol of yttria (3Y-TSZ) is the most used material in the production of dental prostheses (e.g. crowns), due to its high biocompatibility, high mechanical strength, oxidation and abrasion resistance, high hardness and fracture toughness. The machining of crowns can produce a waste of approximately 30% of the initial blank, generating a significant economic loss (∼US 1087/kg) for the prosthetic laboratories. This work describes the beneficiation of zirconia powder resultant from CAD/CAM milling process, and suggests different applications based on the new properties. Is proposed a recycling solution by mixing the residues with commercial powder with 5, 10 and 50 vol% of residues and prepared by dry mixing, then pressed at 100 MPa and sintered at 1500 °C for 2 h. The quality control of the residues included the particle size distribution, the crystalline phases and chemical composition. For the recycled mixtures it was analyzed the color difference, the microstructure and mechanical properties, as Young and Weibull modulus, and flexural strength, to evaluate the potential uses of this new material. These residues can be used without any additional treatment on applications such as zirconia sand blasting for prosthodontics and as raw material for jewelry, pigment and refractory industries. In the case of the recycled mixtures is suggested the use in jewelry applications, taking advantage of their uniform color and mechanical properties which are similar to hardened noble metals alloys. Highlights: Zirconia residues have a high economic value and potential recycling. Zirconia powder residues can be reused as by-product on ceramic industries. Residue can be used without additional treatment for prosthodontic sand blasting. This residue can be remanufactured for jewelry industry. Recycling management of this residue suggest the need of a network of users.